SIGNing a symbiotic treaty with gut microbiota. (3rd March 2015) - Lugo‐Villarino, Geanncarlo; Neyrolles, Olivier
<x xml:space="preserve">Abstract</x> Beneficial microbes hold great promise for the treatment of a wide range of immune and inflammatory disorders. In this issue of The EMBO Journal, Lightfoot and colleagues report how the food‐grade bacterium Lactobacillus acidophilus helps the immune system to limit experimental colitis in mice through interaction between SIGNR3 and surface layer protein A (SlpA) in L. acidophilus. These results pave the way for future development of novel therapies for inflammatory diseases, including inflammatory bowel disease.